A −78dBm sensitivity super-regenerative receiver at 96 GHz with quench-controlled metamaterial oscillator in 65nm CMOS - Shang, Yang (2013)
One high-sensitivity CMOS superregenerative receiver is demonstrated for 96GHz mm-wave imaging based on high-Q metamaterial oscillator. Compared to traditional LC-tank based oscillator, the metamaterial oscillator is developed by folded-differential transmission-line loaded complimentary split-ring resonator (FDTLCSRR). With formed sharp stop-band, standing-wave is established with high EM-energy storage at mm-wave region for high-Q oscillatory amplification. As such, one high-sensitivity 96 GHz super-regenerative receiver is realized in 65nm CMOS with measurement results of: -78 dBm sensitivity, 0.67 fW/Hz0.5 NEP, 8.5 dB NF, 2.8mW power consumption and 0.014 mm2 core area.